2016
DOI: 10.1097/meg.0000000000000677
|View full text |Cite
|
Sign up to set email alerts
|

The use of β-blockers is associated with a lower risk of developing hepatocellular carcinoma in patients with cirrhosis

Abstract: Cirrhotic patients treated with BB have a lower cumulative probability of developing HCC during the 10 years after the diagnosis of cirrhosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 17 publications
2
14
0
Order By: Relevance
“…Other potential effects of beta-blockers upon cirrhotic patients: To further investigate the haemodynamically independent effects of beta-blockade in patients with cirrhosis, Thiele et al[42] performed a meta-analysis of 23 RCTs on 2618 patients finding a reduced incidence of hepatocellular carcinoma (HCC) in patients receiving NSBBs [risk difference 0.026, 95% CI 0.052-0.001, number needed to treat (NNT) 38 patients]. Recently, Herrera et al[43] prospectively evaluated 173 patients included in the early HCC detection program for a median follow-up time of 11 years. The cumulative incidence of HCC was significantly lower in NSBB users compared to non-users (6% vs 19% at 10 years, 16% vs 24% at 15 years), with beta-blockade being the only parameter inversely correlated with HCC development on multivariate analysis.…”
Section: Currently-used Medicationsmentioning
confidence: 99%
“…Other potential effects of beta-blockers upon cirrhotic patients: To further investigate the haemodynamically independent effects of beta-blockade in patients with cirrhosis, Thiele et al[42] performed a meta-analysis of 23 RCTs on 2618 patients finding a reduced incidence of hepatocellular carcinoma (HCC) in patients receiving NSBBs [risk difference 0.026, 95% CI 0.052-0.001, number needed to treat (NNT) 38 patients]. Recently, Herrera et al[43] prospectively evaluated 173 patients included in the early HCC detection program for a median follow-up time of 11 years. The cumulative incidence of HCC was significantly lower in NSBB users compared to non-users (6% vs 19% at 10 years, 16% vs 24% at 15 years), with beta-blockade being the only parameter inversely correlated with HCC development on multivariate analysis.…”
Section: Currently-used Medicationsmentioning
confidence: 99%
“…Some studies reported that NSBB was not associated with increased mortality among decompensated cirrhotic patients with ascites [6][7][8][9], whereas Kalambokis GN, et al [10] found that an increased mortality was observed in Child-Pugh C cirrhotic patients with ascites if using NSBB for more than six months. Moreover, NSBB could reduce cancer risk [11,12], including hepatocellular carcinoma (HCC) [13,14]. The issue about the use of NSBB on the prognosis in compensated cirrhotic patients without major complications has seldom been reported.…”
Section: Introductionmentioning
confidence: 99%
“…One potential explanation for this effect is the reduction in gastrointestinal bleeding by β receptor blockers; another possible explanation is a reduction in the incidence of liver cancer ( 18 ). It was also demonstrated that propranolol reduced the 10-year cumulative incidence of liver cancer in patients with hepatitis C-associated cirrhosis ( 19 ). Liver cancer in patients in China primarily develops from hepatitis B virus (HBV)-associated liver cirrhosis and is frequently accompanied by an increase in α-fetoprotein levels ( 20 22 ).…”
Section: Discussionmentioning
confidence: 99%